2017
DOI: 10.1097/coh.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

Use of direct oral anticoagulants for treatment of atrial fibrillation in patients with HIV

Abstract: Caution is needed when prescribing DOACs in patients with atrial fibrillation and HIV due to potential drug interactions. Studies are lacking and current advice is based on case reports, expert opinion and knowledge of theoretical interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“… 47 Other studies have shown that ritonavir-boosted protease inhibitors seem safe in patients taking dabigatran. 48 , 49 A recent review indicates that the concomitant use of protease inhibitors is contraindicated or not recommended with apixaban, rivaroxaban, and edoxaban but, in the case of dabigatran, although there are limited data, no significant interaction is expected. 50 Another recent review reported that no dose modification is required with the concomitant use of lopinavir/ritonavir and dabigatran, whereas a 50% dose reduction is necessary with apixaban and coadministration is not recommended for edoxaban and rivaroxaban.…”
Section: Oral Anticoagulation and Covid-19 Infectionmentioning
confidence: 99%
“… 47 Other studies have shown that ritonavir-boosted protease inhibitors seem safe in patients taking dabigatran. 48 , 49 A recent review indicates that the concomitant use of protease inhibitors is contraindicated or not recommended with apixaban, rivaroxaban, and edoxaban but, in the case of dabigatran, although there are limited data, no significant interaction is expected. 50 Another recent review reported that no dose modification is required with the concomitant use of lopinavir/ritonavir and dabigatran, whereas a 50% dose reduction is necessary with apixaban and coadministration is not recommended for edoxaban and rivaroxaban.…”
Section: Oral Anticoagulation and Covid-19 Infectionmentioning
confidence: 99%
“…By the same mechanism, NOACs also have interaction with ART drugs . A case of decreased rivaroxaban concentration by concomitant nevirapine administration has been described, as the result of putative CYP3A induction and accelerated drug clearance .…”
Section: Managing Drug–drug Interactions In Patients With Hiv‐1 and Amentioning
confidence: 99%
“…Correspondence Two patients had bleeding complications with concomitant administration of the PI and one developed DVT whilst also on nevirapine. The authors comment on their own successful experience of using dabigatran for AF in more than 20 patients on ART (West et al, 2017). To our knowledge, use of apixaban and edoxaban has not been reported in patients with HIV and there are no reports of the use of DOACs for the treatment of VTE in this patient population.…”
mentioning
confidence: 99%